Envelhecimento e longevidade produtiva sob a perspectiva da psicologia social comunitária: reflexões a partir de duas indústrias de Curitiba – PR - Mercer, Noélly Cristina Harrison (2017)
Aging is a worldwide phenomenon. It occurs in developed countries, like Canada and Germany, and in under developed countries, as Brazil and others from Latin America. People are living more and birth and mortality rates are decreasing. This scenario has reflects in labor market, since people with more than 60 years old are present in companies’, what demands that companies must be prepared to attend the requirements and needs of these workers. At the same time, it demands that government is attentive to this population and able to develop inclusive programs to ensure life quality and longevity to elderly people. This thesis proposes to understand, from the perspective of Social Community Psychology, the actions developed to promote longevity in a private sector organization and in another of the public sector, located in Curitiba. The research was based on a qualitative and exploratory investigation and relies on bibliographic review, documents analysis and interviews, which were analyzed from the Core Meaning perspective, accordingly to Aguiar e Ozella (2006). From these analyses, were identified three Core Meaning: Centrality at work: I have to time for kids; Exclusion of the elderly: eliminate elderly workers and Early retirement: Elderly are induced to quit and retire. While the private company develops a program to prepare the worker to retire and reinsert in the labor market, the public company focuses in actions related only to prepare to retirement. The conclusion is that both organization do not develop actions focused in longevity. The research brings up that there is no care on aging and permanence at work. New studies, expanding the researched universe, needs to be developed for a better understanding of this matter, for the public programs face the new scenario of aging population and the need of extend the lifetime in formal jobs, respecting the features and needs of elderly people.